High-performance special ceramic material and preparation process thereof

By introducing Mo3NiB3 and nickel-plated modified nano-silicon carbide whiskers into the ceramic materials, combined with ball milling and liquid phase sintering processes, the brittleness and oxidation problems of ceramic materials under extreme conditions are solved, and its impact resistance and mechanical properties are improved.

CN119220912APending Publication Date: 2024-12-31HEYUAN FUMA CEMENTED CARBIDE CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411352319.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing ceramic materials are prone to fracture under extreme conditions, have high brittleness and oxidation under high temperature environments, resulting in a decrease in mechanical properties, and the introduced reinforced phase and the interface bonding force between the ceramic materials is insufficient, so it is unable to effectively transfer loads.

Method used

The preparation process of high-performance special ceramic materials is adopted, including the ingredients of tungsten carbide, Mo3NiB3 ternary boronide, nano-silicon carbide whiskers, etc., and the ceramic materials with high hardness and toughness are formed through ball milling, molding and liquid phase sintering. And the interface bonding performance is improved through nickel plating modification.

Benefits of technology

It improves the impact resistance, bending strength and overall mechanical properties of ceramic materials, reduces interfacial microcracks and pores, forms a uniform and fine grain structure, and enhances the toughness and density of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005062678500000101
    Figure BDA0005062678500000101
Patent Text Reader

Abstract

The invention discloses a high-performance special ceramic material and a preparation process thereof, and the preparation process comprises the following steps: proportioning tungsten carbide, ternary boride, titanium nitride, molybdenum, nickel, silicon, cobalt and other raw materials with nano silicon carbide whiskers according to a ratio, carrying out ball milling treatment, adding a forming agent, and continuing ball milling and granulation; and then, carrying out compression molding on the ceramic powder, carrying out liquid phase sintering in a CO atmosphere, and cooling to room temperature to obtain the high-performance special ceramic material. The Mo3NiB3 ternary boride is introduced, so that the hardness and impact resistance of the ceramic material can be improved, the interface bonding force between a ceramic matrix and a reinforcing phase is enhanced, and the bending strength is improved; the nano silicon carbide whiskers are subjected to nickel plating treatment, so that the interface bonding force can be improved, microcracks are reduced, and the strength and toughness of the ceramic material are enhanced; by optimizing the sintering process and adopting a staged heating mode, grain growth can be controlled, and the density and mechanical properties of the ceramic material are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of ceramic materials, and in particular to a high-performance special ceramic material and a preparation process thereof. Background Art

[0002] High-performance special ceramic materials refer to ceramic materials with excellent mechanical properties and special functions, which can maintain stable physical and chemical properties under extreme conditions. Such materials usually have the characteristics of high hardness, high strength, high temperature resistance, corrosion resistance and wear resistance. Due to these excellent properties, high-performance special ceramic materials are widely used in aerospace, cutting tools, molds and other fields.

[0003] In the prior art, although traditional ceramic materials have high hardness and excellent wear resistance, they generally have problems of insufficient toughness and high brittleness, and are prone to breakage under impact or high stress; in addition, ceramic materials are also prone to oxidation and grain growth in high temperature environments, which leads to a decrease in the mechanical properties of ceramic materials and makes it difficult to meet the use requirements under extreme working conditions; in order to improve the mechanical properties of ceramic materials, researchers have tried to introduce reinforcing phases, such as carbides, nitrides and metal elements, into ceramic materials. However, the interface bonding force between the introduced reinforcing phases and the ceramic materials is generally weak, resulting in the inability of the reinforcing phases to effectively transfer loads, which in turn leads to a decrease in the mechanical properties of the ceramic materials.

[0004] Therefore, the prior art has defects and needs to be improved. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a high-performance special ceramic material with high toughness and strong mechanical properties and a preparation process thereof.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] A preparation process of a high-performance special ceramic material comprises the following steps:

[0008] S1. Prepare the raw materials according to the following weight percentages: 60-70wt% tungsten carbide powder, 4-10wt% ternary boride powder, 2-8wt% titanium nitride powder, 5-10wt% molybdenum powder, 5-10wt% nickel powder, 6-12wt% silicon powder, 7-12wt% cobalt powder, and 0.3-2wt% nano silicon carbide whiskers;

[0009] S2, adding the mixed raw materials into a ball mill, and then adding ball milling media for ball milling treatment, the liquid level of the ball milling media is 10-20mm higher than the grinding balls and the mixed raw materials, and after wet milling for 20-30h, 3-8wt% of the molding agent is added to the mixed raw materials, and the ball milling is continued for 4-18h, and then granulated to obtain ceramic powder;

[0010] S3, filtering the ceramic powder obtained in step S2, placing it in a mold for compression molding after drying, and maintaining it at a molding pressure of 5 MPa for 10-30 minutes to obtain a molded body;

[0011] S4. Place the formed body in a sintering furnace in a CO atmosphere for liquid phase sintering. The gas pressure is 1-2Mpa, the sintering temperature is 1420-1480℃, and the insulation time is 1-2h. After the insulation is completed, argon gas is introduced to exhaust the CO gas, and the argon pressure is maintained at 2-4Mpa. After insulation for 20-40min, it is naturally cooled to room temperature to obtain high-performance special ceramic materials.

[0012] Using the above technical solution, the ternary boride is Mo3NiB3.

[0013] By adopting the above-mentioned technical solutions, the nano silicon carbide whiskers are subjected to modification treatment, specifically:

[0014] a. Place the nano-SiC whiskers in a sensitizing solution containing 0.1-0.2 mol / L tin chloride and 0.1-0.2 mol / L sodium chloride for sensitization treatment. The sensitization time is 30-60 min and the temperature is maintained at 55-65° C. so that the tin ions are adsorbed on the surface of the nano-SiC whiskers;

[0015] b. Place the sensitized nano-SiC whiskers in a 0.02-0.05 mol / L silver nitrate activation solution and stir at room temperature for 5-10 minutes. The silver ions will be reduced to metallic silver by the tin ions and deposited on the surface of the nano-SiC whiskers to form catalytic active sites.

[0016] c. Place the activated nano-SiC whiskers in a nickel plating solution, control the temperature at 60-80°C, and react for 40-60 minutes to gradually deposit nickel on the silver catalytic sites on the surface of the nano-SiC whiskers to form a uniform nickel plating layer.

[0017] By adopting the above technical solutions, the components of the nickel plating solution are 20-30 g / L nickel sulfate, 10-20 g / L sodium hypophosphite, and 30-50 g / L sodium acetate, and the pH value of the nickel plating solution is 4.2-4.8.

[0018] By adopting the above technical solutions, in step S4, after the temperature in the sintering furnace is raised to 800-1000°C, it is kept warm for 20-40 minutes, and then raised to the target sintering temperature of 1420-1480°C at a heating rate of 5-15°C for liquid phase sintering.

[0019] By adopting the above technical solutions, in step S2, the ball milling medium is one of gasoline, acetone, ethane or anhydrous ethanol.

[0020] By adopting the above technical solutions, in step S2, the weight ratio of the grinding balls to the mixed raw materials is 4-5:1, and the grinding balls are cemented carbide balls or steel balls.

[0021] By adopting the above-mentioned technical solutions, in step S2, the molding agent is a mixture of polyvinyl alcohol and zinc stearate, and the volume ratio of the polyvinyl alcohol to zinc stearate is 1:2.

[0022] By adopting the above-mentioned technical solutions, the purity of the nano-silicon carbide whiskers is ≥99wt%.

[0023] The technical solution also provides a high-performance special ceramic material, which is prepared using any of the above-mentioned preparation processes for the high-performance special ceramic material.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention introduces Mo3NiB3 ternary boride, which can effectively improve the impact resistance of ceramic materials while improving the hardness of the material; and the crystal structure of MoNiB helps to form a strong bond with other hard phases, improve the interface bonding strength between the ceramic matrix and the reinforcement phase, and thus improve the bending strength and overall mechanical properties of the ceramic material; by performing nickel plating modification on the nano-silicon carbide whiskers, a metal nickel plating layer can be formed on the surface of the nano-silicon carbide whiskers, and the metal nickel plating layer can greatly improve the interface bonding performance between the nano-silicon carbide whiskers and the ceramic matrix, thereby reducing microcracks or pores at the interface and improving the strength and toughness of the composite material; during the sintering process, when the temperature in the sintering furnace is raised to 800-1000°C, the temperature is kept for 20-4 0min, and then increase the temperature to the target sintering temperature of 1420-1480℃ at a heating rate of 5-15℃ for liquid phase sintering. In the temperature range of 800-1000℃, the organic components in the ceramic material can be completely decomposed and volatilized, and at the same time, a small amount of low-temperature sintering reaction begins. By keeping warm at this temperature, the particles in the ceramic matrix material can be pre-sintered to perform preliminary densification, ensuring that the internal pores and impurities can be eliminated to the greatest extent before entering the liquid phase sintering, avoiding material defects caused by premature sintering; by gradually increasing the temperature to the target sintering temperature at a slower heating rate, the rapid growth of the grains can be suppressed, so that the sintered ceramic material has a more uniform and fine grain structure, thereby improving the strength and toughness of the product. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0027] The present invention provides a preparation process of a high-performance special ceramic material, comprising the following steps:

[0028] S1. Mix the raw materials according to the following weight percentages: 60-70wt% tungsten carbide powder, 4-10wt% ternary boride powder, 2-8wt% titanium nitride powder, 5-10wt% molybdenum powder, 5-10wt% nickel powder, 6-12wt% silicon powder, 7-12wt% cobalt powder, and 0.3-2wt% nano silicon carbide whiskers. Tungsten carbide is the main hard phase in ceramic materials, accounting for the highest proportion, so that the ceramic material has sufficient hardness and strength. Too low a tungsten carbide content will result in insufficient wear resistance of the ceramic material, while too high a content may increase the brittleness of the ceramic material. Ternary boride has high strength. , wear resistance and high temperature resistance, which can improve the crack resistance and heat resistance of ceramic materials, and can also enhance the material's oxidation resistance; nitriding can improve the wear resistance and hardness of ceramic materials; cobalt has excellent toughness and wear resistance at high temperatures, and can form a good bonding phase with tungsten carbide and titanium nitride, thereby enhancing the impact resistance and wear resistance of ceramic materials; nano-silicon carbide whiskers have extremely high strength, hardness and heat resistance, which can significantly improve the fracture toughness, flexural strength and crack resistance of ceramic materials. Nano-scale silicon carbide whiskers enable them to be evenly distributed in the ceramic matrix, preventing stress concentration and reducing the brittleness of ceramic materials.

[0029] S2. Add the mixed raw materials into a ball mill, then add ball milling media for ball milling, the liquid level of the ball milling media is 10-20mm higher than the grinding balls and the mixed raw materials, and after wet grinding in the ball mill for 20-30h, add 3-8wt% of the molding agent into the mixed raw materials, continue ball milling for 4-18h, and then granulate to obtain ceramic powder; the ball milling process can refine the raw material particles to a fine particle size, thereby improving the density and sintering performance of the ceramic material; the ball milling medium can play a lubricating role, reduce frictional heat, and prevent particle agglomeration. The liquid level of the ball milling medium is 10-20mm higher than the grinding balls and raw materials, so that the ball milling medium can completely infiltrate the grinding balls and raw materials, avoiding uneven grinding caused by dry grinding; the molding agent can provide sufficient lubricity during pressing, so that the ceramic powder is easier to flow during the pressing process, and the particles are evenly distributed, thereby improving the molded density of the formed body.

[0030] S3. Filter the ceramic powder obtained in step S2, place it in a mold for compression molding after drying, and maintain it at a molding pressure of 5 MPa for 10-30 minutes to obtain a molded body; a pressure of 5 MPa can make the ceramic powder reach a higher density during molding, so that the particles are in close contact; it should be noted that when the pressure is too low, it is easy to cause the molded body to be not dense enough, affecting the mechanical properties after subsequent sintering; when the pressure is too high, it will cause the powder in the molded body to be over-pressurized and cause structural damage.

[0031] S4. Place the formed body in a sintering furnace in a CO atmosphere for liquid phase sintering. The gas pressure is 1-2Mpa, the sintering temperature is 1420-1480℃, and the insulation time is 1-2h. After the insulation is completed, argon gas is introduced to exhaust the CO gas, and the argon pressure is maintained at 2-4Mpa. After insulation for 20-40min, it is naturally cooled to room temperature to obtain high-performance special ceramic materials. During the high-temperature sintering process, the metal elements in the ceramic material are prone to oxidation reactions, resulting in a decrease in the performance of the ceramic material. By introducing CO gas during sintering, the oxidation of the material can be prevented, ensuring that the ceramic material maintains high hardness and wear resistance at high temperatures; appropriate gas pressure can promote particle rearrangement during the sintering process and increase liquid phase flow, thereby filling the pores in the formed body and improving the density of the ceramic material; at a sintering temperature of 1420-1480°C, the metal phases in the ceramic material, such as cobalt and nickel, will partially melt to form a liquid phase. The appearance of the liquid phase can facilitate the particle rearrangement and densification of the material, reduce the pores in the formed body, and thus enhance the strength and toughness of the ceramic material; after the CO gas is discharged, by maintaining an argon pressure of 2-4MPa and keeping warm for 20-40min, the further densification and solid phase diffusion of the ceramic material can be promoted to form a high-density, uniform microstructure.

[0032] Furthermore, the ternary boride is Mo3NiB3. As a hard phase, Mo3NiB3 has good toughness and strength. Compared with traditional binary borides, the ternary structure of Mo3NiB3 can effectively improve the impact resistance of ceramic materials while improving the hardness of the material; and the crystal structure of Mo3NiB3 helps to form a strong bond with other hard phases, improve the interface bonding strength between the ceramic matrix and the reinforcement phase, and thus improve the bending strength and overall mechanical properties of the ceramic material.

[0033] Furthermore, the nano silicon carbide whiskers are subjected to a modification treatment, specifically:

[0034] a. Place the nano-SiC whiskers in a sensitizing solution containing 0.1-0.2 mol / L tin chloride and 0.1-0.2 mol / L sodium chloride for sensitization treatment. The sensitization time is 30-60 min and the temperature is maintained at 55-65° C. so that the tin ions are adsorbed on the surface of the nano-SiC whiskers;

[0035] b. Place the sensitized nano-SiC whiskers in a 0.02-0.05 mol / L silver nitrate activation solution and stir at room temperature for 5-10 minutes. The silver ions will be reduced to metallic silver by the tin ions and deposited on the surface of the nano-SiC whiskers to form catalytic active sites.

[0036] c. Place the activated nano-SiC whiskers in a nickel plating solution, control the temperature at 60-80°C, and react for 40-60 minutes to gradually deposit nickel on the silver catalytic sites on the surface of the nano-SiC whiskers to form a uniform nickel plating layer.

[0037] By sensitizing and activating the nano-silicon carbide whiskers, active sites of metallic silver can be formed on the surface of the nano-silicon carbide whiskers through chemical adsorption and reduction reactions. These active sites can prevent the nano-silicon carbide whiskers from agglomerating in the composite ceramic material matrix, so that the nano-silicon carbide whiskers can be evenly dispersed in the ceramic material matrix. By nickel plating, a metallic nickel coating can be formed on the surface of the nano-silicon carbide whiskers. The metallic nickel coating can greatly improve the interfacial bonding properties between the nano-silicon carbide whiskers and the ceramic matrix, reduce microcracks or pores at the interface, and thereby improve the strength and toughness of the composite material.

[0038] Furthermore, the nickel plating solution comprises 20-30 g / L of nickel sulfate, 10-20 g / L of sodium hypophosphite, and 30-50 g / L of sodium acetate, and the pH value of the nickel plating solution is 4.2-4.8. Nickel sulfate is the source of nickel ions in the nickel plating solution, which provides nickel ions for reduction to metallic nickel during the reaction and deposition on the surface of the nano-silicon carbide whiskers; sodium hypophosphite is a reducing agent for the nickel plating reaction, which can reduce the nickel ions in the nickel plating solution to metallic nickel; sodium acetate is a buffer in the nickel plating solution, which can adjust the pH value of the nickel plating solution to avoid affecting the deposition rate of nickel ions and the formation quality of the coating.

[0039] Furthermore, in step S4, after the temperature in the sintering furnace is raised to 800-1000°C, it is kept warm for 20-40 minutes, and then the temperature is raised to the target sintering temperature of 1420-1480°C at a heating rate of 5-15°C for liquid phase sintering. In the temperature range of 800-1000°C, the organic components in the ceramic material can be completely decomposed and volatilized, and at the same time, a trace amount of low-temperature sintering reaction begins. By keeping warm at this temperature, the particles in the ceramic matrix material can be pre-sintered to perform preliminary densification, ensuring that the internal pores and impurities can be eliminated to the greatest extent before entering the liquid phase sintering, avoiding material defects caused by premature sintering; by gradually raising the temperature to the target sintering temperature at a slower heating rate, the excessive growth of the grains can be suppressed, so that the sintered ceramic material has a more uniform and fine grain structure, thereby improving the strength and toughness of the product.

[0040] Furthermore, in step S2, the ball milling medium is one of gasoline, acetone, ethane or anhydrous ethanol. Gasoline, acetone, ethane or anhydrous ethanol has good fluidity and volatility, and can fully wet the ceramic powder during the ball milling process to prevent agglomeration between particles and ensure uniform dispersion between powder particles; and gasoline, acetone, ethane or anhydrous ethanol, as an organic solvent or inert medium, can isolate oxygen in the air during the ball milling process to prevent highly active ingredients, such as molybdenum, silicon carbide, etc., from being oxidized during the ball milling process.

[0041] Furthermore, in step S2, the weight ratio of the grinding balls to the mixed raw materials is 4-5:1, and the grinding balls are carbide balls or steel balls. Such a setting can improve the ball milling efficiency and the degree of powder refinement, ensure the uniformity of the powder particles, avoid particle agglomeration, and improve the density of the ceramic material.

[0042] Further, in step S2, the molding agent is a mixture of polyvinyl alcohol and zinc stearate, and the volume ratio of polyvinyl alcohol to zinc stearate is 1:2. The introduction of polyvinyl alcohol can improve the adhesion between powder particles, ensure that the particles can combine with each other during molding, and form a relatively dense molding body; zinc stearate, as an organic lubricant, can effectively reduce the friction between the ceramic powder particles and the mold, reduce the sticking phenomenon during the pressing process, thereby improving the demolding performance of the molded body, and preventing the molded body from cracking or defecting during demolding; setting the volume ratio of polyvinyl alcohol to zinc stearate to 1:2 can provide sufficient bonding force and ensure good lubricity, ensuring that the ceramic powder has sufficient strength and demolding performance during the molding process, thereby optimizing the molding effect.

[0043] Furthermore, the purity of the nano-silicon carbide whiskers is ≥99wt%.

[0044] Example 1

[0045] Embodiment 1 of the present invention provides a process for preparing a high-performance special ceramic material, comprising the following steps:

[0046] S1. Prepare the raw materials according to the following weight percentages: 66wt% tungsten carbide powder, 4wt% Mo3NiB3 powder, 4wt% titanium nitride powder, 5wt% molybdenum powder, 6wt% nickel powder, 6wt% silicon powder, 8wt% cobalt powder, and 1wt% nano-silicon carbide whiskers;

[0047] Wherein, the purity of the nano-silicon carbide whiskers is ≥99wt%, and the nano-silicon carbide whiskers are subjected to a modification treatment, specifically:

[0048] a. Place the nano-SiC whiskers in a sensitizing solution containing 0.1 mol / L tin chloride and 0.1 mol / L sodium chloride for sensitization treatment. The sensitization time is 60 min and the temperature is maintained at 65°C so that the tin ions are adsorbed on the surface of the nano-SiC whiskers;

[0049] b. Place the sensitized nano-SiC whiskers in a 0.02 mol / L silver nitrate activation solution and stir at room temperature for 10 min. The silver ions will be reduced to metallic silver by the tin ions and deposited on the surface of the nano-SiC whiskers to form catalytic active sites.

[0050] c. placing the activated nano-SiC whiskers in a nickel plating solution, controlling the temperature at 60° C. for 60 min, so as to gradually deposit nickel on the silver catalytic sites on the surface of the nano-SiC whiskers to form a uniform nickel plating layer;

[0051] The components of the nickel plating solution are 20 g / L nickel sulfate, 10 g / L sodium hypophosphite, and 30 g / L sodium acetate, and the pH value of the nickel plating solution is 4.2.

[0052] S2, adding the mixed raw materials into a ball mill, and then adding ball milling medium for ball milling treatment, the liquid level of the ball milling medium is 10 mm higher than the grinding balls and the mixed raw materials, the ball milling medium is anhydrous ethanol, the weight ratio of the grinding balls to the mixed raw materials is 4:1, the grinding balls are cemented carbide balls, after wet milling in the ball mill for 20 hours, 3 wt% of the forming agent is added to the mixed raw materials, and the ball milling is continued for 18 hours, and then granulated to obtain ceramic powder;

[0053] Wherein, the molding agent is a mixture of polyvinyl alcohol and zinc stearate, and the volume ratio of the polyvinyl alcohol to zinc stearate is 1:2.

[0054] S3, filtering the ceramic powder obtained in step S2, placing it in a mold for compression molding after drying, and maintaining it at a molding pressure of 5 MPa for 30 minutes to obtain a molded body;

[0055] S4. Place the formed body in a sintering furnace in a CO atmosphere for liquid phase sintering with a gas pressure of 1Mpa. When the temperature in the sintering furnace is raised to 800°C, keep it warm for 40 minutes, then increase the temperature to 1420°C at a heating rate of 15°C for liquid phase sintering for 1 hour. After the insulation is completed, argon gas is introduced to exhaust the CO gas and the argon pressure is maintained at 2Mpa. After keeping warm for 40 minutes, naturally cool to room temperature to obtain high-performance special ceramic materials.

[0056] Example 2

[0057] Embodiment 2 of the present invention provides a process for preparing a high-performance special ceramic material, comprising the following steps:

[0058] S1. Prepare the raw materials according to the following weight percentages: 60wt% tungsten carbide powder, 9wt% Mo3NiB3 powder, 4wt% titanium nitride powder, 5wt% molybdenum powder, 7wt% nickel powder, 6wt% silicon powder, 7wt% cobalt powder, and 2wt% nano silicon carbide whiskers;

[0059] Wherein, the purity of the nano-silicon carbide whiskers is ≥99wt%, and the nano-silicon carbide whiskers are subjected to a modification treatment, specifically:

[0060] a. Place the nano-SiC whiskers in a sensitizing solution containing 0.1 mol / L tin chloride and 0.1 mol / L sodium chloride for sensitization treatment. The sensitization time is 30 min and the temperature is maintained at 65°C so that the tin ions are adsorbed on the surface of the nano-SiC whiskers;

[0061] b. Place the sensitized nano-SiC whiskers in a 0.05 mol / L silver nitrate activation solution and stir at room temperature for 10 min. The silver ions will be reduced to metallic silver by the tin ions and deposited on the surface of the nano-SiC whiskers to form catalytic active sites.

[0062] c. placing the activated nano-SiC whiskers in a nickel plating solution, controlling the temperature at 80°C and the reaction time at 60 minutes, so as to gradually deposit nickel on the silver catalytic sites on the surface of the nano-SiC whiskers to form a uniform nickel plating layer;

[0063] The components of the nickel plating solution are 30 g / L nickel sulfate, 20 g / L sodium hypophosphite, and 50 g / L sodium acetate, and the pH value of the nickel plating solution is 4.8.

[0064] S2, adding the mixed raw materials into a ball mill, and then adding ball milling media for ball milling, the liquid level of the ball milling media is 20 mm higher than the grinding balls and the mixed raw materials, the ball milling medium is gasoline, the weight ratio of the grinding balls to the mixed raw materials is 5:1, the grinding balls are steel balls, after wet milling for 30 hours, 8 wt% of the forming agent is added to the mixed raw materials, and the ball milling is continued for 18 hours, and then granulated to obtain ceramic powder;

[0065] Wherein, the molding agent is a mixture of polyvinyl alcohol and zinc stearate, and the volume ratio of the polyvinyl alcohol to zinc stearate is 1:2.

[0066] S3, filtering the ceramic powder obtained in step S2, placing it in a mold for compression molding after drying, and maintaining it at a molding pressure of 5 MPa for 30 minutes to obtain a molded body;

[0067] S4. Place the formed body in a sintering furnace in a CO atmosphere for liquid phase sintering with a gas pressure of 2Mpa. When the temperature in the sintering furnace is raised to 1000°C, keep it warm for 20 minutes, then increase the temperature to 1480°C at a heating rate of 5°C for liquid phase sintering for 2 hours. After the insulation is completed, argon gas is introduced to exhaust the CO gas and the argon pressure is maintained at 4Mpa. After keeping warm for 20 minutes, it is naturally cooled to room temperature to obtain high-performance special ceramic materials.

[0068] Comparative Example 1

[0069] The high performance special ceramic material and preparation process thereof of Comparative Example 1 are different from those of Example 1 in that in step S1 , no ternary boride powder is added.

[0070] Comparative Example 2

[0071] The high-performance special ceramic material and its preparation process of Comparative Example 2 are different from those of Example 1 in that in step S1, nano silicon carbide whiskers are not added.

[0072] Comparative Example 3

[0073] The high-performance special ceramic material and its preparation process of comparative example 3 are different from those of example 1 in that in step S1, the nano-silicon carbide whiskers are not subjected to nickel plating modification treatment.

[0074] Comparative Example 4

[0075] The high performance special ceramic material and its preparation process of comparative example 4 are different from those of example 1 in that in step S2, no forming agent is added during the ball milling process.

[0076] Comparative Example 5

[0077] The high performance special ceramic material and its preparation process of comparative example 5 are different from those of example 1 in that in step S4, CO gas is not introduced into the sintering furnace.

[0078] Comparative Example 6

[0079] The high performance special ceramic material and its preparation process of comparative example 6 are different from those of example 1 in that in step S4, the sintering temperature is 1360°C.

[0080] The following experiments are conducted on the above-mentioned embodiments 1-2 and comparative examples 1-6 to verify or understand their performance. In the high-performance special ceramic materials prepared in the above-mentioned embodiments 1-2 and comparative examples 1-6.

[0081]

[0082] Table 1 Comparison of performance tests of high performance special ceramic materials of various embodiments and comparative examples

[0083] According to Table 1 above, it can be seen that in the high-performance special ceramic materials prepared in Example 1 and Example 2, by introducing Mo3NiB3 ternary boride, the hardness of the material can be improved while the impact resistance of the ceramic material can be effectively improved; and the crystal structure of MoNiB helps to form a strong bond with other hard phases, improve the interface bonding strength between the ceramic matrix and the reinforcement phase, and thus improve the bending strength and overall mechanical properties of the ceramic material; by nickel-plating modification of the nano-silicon carbide whiskers, a metal nickel coating can be formed on the surface of the nano-silicon carbide whiskers, and the metal nickel coating can greatly improve the interface bonding performance between the nano-silicon carbide whiskers and the ceramic matrix, thereby reducing microcracks or pores at the interface and improving the strength and toughness of the composite material; during the sintering process, when the temperature in the sintering furnace is raised to 80 After 0-1000℃, keep warm for 20-40min, then increase the temperature to the target sintering temperature of 1420-1480℃ at a heating rate of 5-15℃ for liquid phase sintering. In the temperature range of 800-1000℃, the organic components in the ceramic material can be completely decomposed and volatilized, and at the same time, a small amount of low-temperature sintering reaction begins. By keeping warm at this temperature, the particles in the ceramic matrix material can be pre-sintered for initial densification to ensure that the internal pores and impurities can be eliminated to the greatest extent before entering the liquid phase sintering, avoiding material defects caused by premature sintering; by gradually increasing the temperature to the target sintering temperature at a slower rate, the rapid growth of the grains can be suppressed, so that the sintered ceramic material has a more uniform and fine grain structure, thereby improving the strength and toughness of the product.

[0084] In Comparative Example 1, no ternary boride powder was added to the raw material, which resulted in the ceramic material being more susceptible to cracks and fractures under impact or high stress conditions, and the toughness of the ceramic material was reduced and the brittleness was high;

[0085] In Comparative Example 2, nano silicon carbide whiskers were not added to the raw materials, resulting in stress concentration in the ceramic material when subjected to stress, and cracks tended to expand rapidly in the stress concentration area, thereby increasing the brittleness of the ceramic material and reducing the impact resistance.

[0086] In Comparative Example 3, the nano-silicon carbide whiskers were not subjected to nickel plating modification treatment, and the interface bonding between the silicon carbide whiskers that were not subjected to nickel plating and the ceramic matrix was poor, resulting in microcracks or voids that were easily generated at the interface, affecting the overall mechanical properties of the ceramic material, especially reducing the bending strength and fracture toughness;

[0087] In comparative example 4, in step S2, no molding agent was added during the ball milling process, resulting in reduced fluidity of the ceramic powder, easy adhesion or agglomeration of the powder particles, and uneven filling of the powder in the mold, which affected the uniformity and density of the molded body, thereby reducing the overall performance of the ceramic material;

[0088] In Comparative Example 5, in step S4, CO gas is not introduced into the sintering furnace. If CO gas is not introduced, oxygen or an oxidizing atmosphere will exist in the sintering furnace, causing the metal phase in the ceramic material to undergo an oxidation reaction to generate metal oxides, thereby reducing its mechanical properties. The generation of oxides will also cause embrittlement, resulting in a decrease in the hardness, toughness and strength of the ceramic material.

[0089] In Comparative Example 6, in step S4, the sintering temperature is 1360°C. At a temperature of 1360°C, sufficient liquid phase cannot be formed during the sintering process, resulting in incomplete densification during the sintering process. A large number of pores and voids will appear inside the ceramic material, affecting the overall mechanical properties of the ceramic material, especially the flexural strength and compressive strength.

[0090] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A preparation process of high-performance special ceramic materials, characterized in that: The following steps are involved: S1. Prepare the raw materials according to the following weight percentages: 60-70wt% tungsten carbide powder, 4-10wt% ternary boride powder, 2-8wt% titanium nitride powder, 5-10wt% molybdenum powder, 5-10wt% nickel powder, 6-12wt% silicon powder, 7-12wt% cobalt powder, and 0.3-2wt% nano silicon carbide whiskers; S2, adding the mixed raw materials into a ball mill, and then adding ball milling media for ball milling treatment, the liquid level of the ball milling media is 10-20mm higher than the grinding balls and the mixed raw materials, and after wet milling for 20-30h, 3-8wt% of the molding agent is added to the mixed raw materials, and the ball milling is continued for 4-18h, and then granulated to obtain ceramic powder; S3, filtering the ceramic powder obtained in step S2, placing it in a mold for compression molding after drying, and maintaining it at a molding pressure of 5 MPa for 10-30 minutes to obtain a molded body; S4. Place the formed body in a sintering furnace in a CO atmosphere for liquid phase sintering. The gas pressure is 1-2Mpa, the sintering temperature is 1420-1480℃, and the insulation time is 1-2h. After the insulation is completed, argon gas is introduced to exhaust the CO gas, and the argon pressure is maintained at 2-4Mpa. After insulation for 20-40min, it is naturally cooled to room temperature to obtain high-performance special ceramic materials.

2. The preparation process of high-performance special ceramic material according to claim 1, characterized in that: The ternary boride is Mo3NiB3.

3. The preparation process of high-performance special ceramic material according to claim 1, characterized in that: The nano silicon carbide whiskers are subjected to a modification process, specifically: a. Place the nano-SiC whiskers in a sensitizing solution containing 0.1-0.2 mol / L tin chloride and 0.1-0.2 mol / L sodium chloride for sensitization treatment. The sensitization time is 30-60 min and the temperature is maintained at 55-65° C. so that the tin ions are adsorbed on the surface of the nano-SiC whiskers; b. Place the sensitized nano-SiC whiskers in a 0.02-0.05 mol / L silver nitrate activation solution and stir at room temperature for 5-10 minutes. The silver ions will be reduced to metallic silver by the tin ions and deposited on the surface of the nano-SiC whiskers to form catalytic active sites. c. Place the activated nano-SiC whiskers in a nickel plating solution, control the temperature at 60-80°C, and react for 40-60 minutes to gradually deposit nickel on the silver catalytic sites on the surface of the nano-SiC whiskers to form a uniform nickel plating layer.

4. The preparation process of high-performance special ceramic material according to claim 3, characterized in that: The components of the nickel plating solution are 20-30 g / L of nickel sulfate, 10-20 g / L of sodium hypophosphite, and 30-50 g / L of sodium acetate, and the pH value of the nickel plating solution is 4.2-4.

8.

5. The preparation process of high-performance special ceramic material according to claim 1, characterized in that: In step S4, after the temperature in the sintering furnace is raised to 800-1000°C, it is kept at this temperature for 20-40 minutes, and then raised to the target sintering temperature of 1420-1480°C at a heating rate of 5-15°C for liquid phase sintering.

6. The preparation process of high-performance special ceramic material according to claim 1, characterized in that: In step S2, the ball milling medium is one of gasoline, acetone, ethane or anhydrous ethanol.

7. The preparation process of high performance special ceramic material according to claim 1, characterized in that: In step S2, the weight ratio of the grinding balls to the mixed raw materials is 4-5:1, and the grinding balls are cemented carbide balls or steel balls.

8. The preparation process of high-performance special ceramic material according to claim 1, characterized in that: In step S2, the molding agent is a mixture of polyvinyl alcohol and zinc stearate, and the volume ratio of the polyvinyl alcohol to zinc stearate is 1:

2.

9. The preparation process of high-performance special ceramic material according to claim 1, characterized in that: The purity of the nano-silicon carbide whisker is ≥99wt%.

10. A high-performance special ceramic material, characterized in that: The high-performance special ceramic material is prepared by the preparation process of any one of claims 1 to 9.

Citation Information

Cited By

  • Special ceramic material as well as preparation method and application thereof

    CN120004644A

  • High-strength building ceramic material and preparation method thereof

    CN120289164A

  • High-strength impact-resistant glass product and preparation method thereof

    CN122079493A